Cartography (and Geoinformation) in Education in Austria - Mirjanka Lechthaler (Kartografija i Geoinformacije, 2006)
The basic task of cartography lies in efficient and impeccable transfer of spatial information via cartographic models of geospace. Wired and wireless communication networks serve this purpose. They offer new media possibilities of saving and transferring cartographic information and cartographic models, and therefore their use. This is related to the emphasis of research work and education, which is equally oriented toward theoretical issues and those concerning applied cartography. The paper features a review of cartographic education and accomplished qualifications at universities and professional schools (Fachhochschule) in Austria and a review of newly introduced study programs of Bachelor and Master studies according to guidelines of the Bologna Declaration. The education plan for the instruction of cartography for both studies at the Vienna University of Technology is presented in detail.